Identifying the role of soil microbes in plant invasions. (September 2016) - Dawson, Wayne; Schrama, Maarten
Summary: Understanding how invasions by exotic plant species occur has been and still is a fundamental goal in the field of invasion ecology. Recently, research focus has shifted to below‐ground mechanisms of invasion, which has provided valuable insights into the role of soil microbes in the invasion process. Research on how soil microbes drive plant invasions has produced a multitude of potential mechanisms and hypotheses, and we have taken this timely opportunity to organize these hypotheses, explore interrelations among them and with other drivers of invasion and identify areas requiring more in‐depth study. Synthesis . This special feature brings together current research on soil microbes as drivers and responders of invasion, highlighting the methods that can be used to advance our understanding of how, when and which soil microbes play a role in the invasion process. Further advances in the field can be made by increasing realism in experiments, making wider use of molecular methods and culturing of microbial isolates and considering the importance of microbes relative to other invasion drivers. Abstract : This special feature brings together current research on soil microbes as drivers and responders of invasion, highlighting the methods that can be used to advance our understanding of how, when and which soil microbes play a role in the invasion process. Further advances in the field can be made by increasing realism in experiments, making wider use of molecular methods and culturing of microbial isolates and considering the importance of microbes relative to other invasion drivers.